Participation in Educational Administration of Kaeng Khoi District Basic Education Institution Boards under the Jurisdiction of Saraburi Primary Educational Service Area District Office 2 - Thuanwong, Apichart; Touchumnong , Wiwat (Journal for Developing the Social and Community, 2022)
The research purposes were: (10 to study the participation in educational administration of Kaeng Khoi District Basic Education Institution Boards under the jurisdiction of Saraburi Primary Educational Service Area District Office 2; and (2) to compare the participation in educational administration of Kaeng Khoi District Basic Education Institution Boards under the jurisdiction of Saraburi Primary Educational Service Area District Office 2, classified by gender, age, and education level. The population was the teachers and student parents of schools in Kaeng Khoi District under the jurisdiction of Saraburi Primary Educational Service Area District Office 2; the sample group was the 222 teachers and student parents. The data collection instrument was the 5-level estimate rating scale questionnaire, 32 items, with reliability .86. The data analysis statistics were the percentage, mean, standard deviation, and analysis of variance (F-test). The research findings were: The participation in educational administration of Kaeng Khoi District Basic Education Institution Boards under the jurisdiction of Saraburi Primary Educational Service Area District Office 2 found the overall and each aspect were at the low level. The descending mean were the general administration aspect, the budget administration aspect, the academic administration aspect, and the personnel administration aspect, respectively. The participation in educational administration of Kaeng Khoi District Basic Education Institution Boards under the jurisdiction of Saraburi Primary Educational Service Area District Office 2, classified by gender, age, and education level found the overall and each aspect did not different.